Qualitative analysis with ATLAS.ti 22 in Social Sciences: New tools and concrete applications - Ramiro Pérez Ripossio (Perspectivas Metodológicas​)
This article analyzes the main functions of the ATLAS.ti 22 software in reference to a doctoral research already concluded. This research qualitatively addressed the migratory projects of South American transvestites/trans residing in the AMBA. 44 individual interviews were carried out with the migrants using the Grounded Theory as the main method. The article provides the use of the main functions of this version of the software in order to make other researchers aware of its developments. Thus, the following resources are developed: concept clouds, sentiment analysis, folders, opinion extraction and co-occurrence tables.